Daya Hasil dan Stabilitas Ratun Galur Padi pada Lahan Pasang Surut - Sinaga, Parlin H.; Trikoesoemaningtyas, Trikoesoemaningtyas; Sopandie, Didy; Aswidinnoor, Hajrial (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
The study was aimed to determine the productivity and yield stability of ratoon rice genotypes in three environments and to obtain rice genotypes suistable for ratoonning on specific environment of tidal land. The experiment was designed in a randomized complete block with three replicates. Seedling was planted at 21 days old with spacing of 20 x 20 cm, one seedling per hill. Plants were harvested 30 days after heading by cutting at a height of 10 cm from the soil surface. One day after harvest, the land was irrigated as high as 3 cm and fertilized with Urea 50 kg/ha, TSP 30 kg/ha, and KCl 25 kg/ha. Yield stability was analyzed according to Eberhart and Russel (1966). Ratoons were sensitive to the environmental changes. Genotype IPB97-F-13-1-1, IPB 4S, and IPB 3S produced the main crop + ratoon grain yield of 5.26 t/ha, 5.14 t/ha, and 5.64 t/ha dry milling grain (DMG), respectively. Based on yield of the main crop + ratoon, IPB97-F-13-1-1 and IPB 4S was each considered as adaptable to the suboptimum condition (bi<1). Ratoon crop yield of genotype IPB97-F-13-1-1, IPB 4S, and IPB 3S each was the highest in three locations. The ratoon crop contribution to the rice production was from 31.3% to 61.9% to the main crop.